An Approach to Incorporating Psychology into Economics - Rabin, Matthew (American Economic Review, 2013)
This article proposes an approach to improving the psychological realism of economics while maintaining its conventional techniques and goals–formal theoretical and empirical analysis using tractable models, with a focus on prediction and estimation. Besides tolerating the imperfections that come with precision, models should aim for two crucial criteria: power and scope. The approach advocated is to develop portable extensions of existing models that embed preexisting theories as parameter values, while introducing the new psychological assumptions as alternative parameter values, and make the model portable by defining it in all cases where existing models make predictions.